N-Glycosylation of the Na+-Taurocholate Cotransporting Polypeptide (NTCP) Determines Its Trafficking and Stability and Is Required for Hepatitis B Virus Infection. - Monique D Appelman; Anindita Chakraborty; Ulrike Protzer; Jane A McKeating; Stan F J van de Graaf (PLoS ONE)
The sodium/bile acid cotransporter NTCP was recently identified as a receptor for hepatitis B virus (HBV). NTCP is glycosylated and the role of glycans in protein trafficking or viral receptor activity is not known. NTCP contains two N-linked glycosylation sites and asparagine amino acid residues N5 and N11 were mutated to a glutamine to generate NTCP with a single glycan (NTCP-N5Q or NTCP- N11Q) or no glycans (NTCP- N5,11Q). HepG2 cells expressing NTCP with a single glycan supported HBV infection at a comparable level to NTCP-WT. The physiological function of NTCP, the uptake of bile acids, was also not affected in cells expressing these single glycosylation variants, consistent with their trafficking to the plasma membrane. However, glycosylation-deficient NTCP (NTCP-N5,11Q) failed to support HBV infection, showed minimal cellular expression and was degraded in the lysosome. This affected the physiological bile acid transporter function of NTCP-N5,11Q in a similar fashion. In conclusion, N-glycosylation is required for efficient NTCP localization at the plasma membrane and subsequent HBV infection and these characteristics are preserved in NTCP carrying a single carbohydrate moiety.